Using high-intensity interval training exercises to improve speed and its impact on passing the fitness test for basketball referees (Journal of the College of Basic Education, 2022)
The process of preparing the referee and rehabilitating him physically is among the important topics and matters that The International Basketball Federation attaches great weight to it, as it put a physical fitness test that is difficult He cannot be overrun by any referee easily, unless the referee is physically prepared. through which he can pass that test, hence the importance of research in developing exercises